(untitled) (Epidemiology, Biostatistics, and Public Health, 2024)
Background: Port activities can cause negative socio-environmental impacts, with air quality degradation being one of them. Objective: This study aimed to analyze a potential relationship between environmental air pollutants detected by the Environmental Company of the State of Sao Paulo (CETESB) air quality analysis station, located in Ponta da Praia, Santos and the occurrence of health events related to respiratory diseases. Methods: At the CETESB “Santos – Ponta da Praia” station, from January 2021 to December 2022, monthly cumulative measurement of PM2.5 and PM10, SO2, NO, NOx and NO2 inhalable particles were collected. Additionally, respiratory health events were verified through data from Unified Health System (SUS) database in the State of São Paulo from January 2021 to December 2022. Results: The monthly averages SO2 and NO2 levels did not exceed the limits, but PM2.5 levels exceed twice in July 2021 and 2022, and PM10 levels exceeded four times in May, June and July 2021 and July 2022. Although air quality measured by CETESB station was classified as good, a moderate correlation was identified between NO2 emission and events of pneumonia, bronchitis, and chronic obstructive pulmonary disease events, especially among vulnerable population, up to 19 years old. Conclusions: The results are significant for understanding the relationship between respiratory diseases and air pollution in the Port of Santos area.